Cadastre 2014: Performance of Nepal - Dangol, Susheel; Bhatta, Ganesh Prasad (Journal on Geoinformatics, Nepal, 2018)
International Federation of Surveyors (FIG) is the federation of different nation's member associations representing the interests of surveyors in the professional fields of global surveying, geomatics, geodesy and geo-information. Technical work of FIG is led by ten different commissions with individual themes. Among these commissions, 7th commission with the theme "Cadastre and Land Management" decided to make a vision for cadastre in 20th FIG congress in 1994 and in line with this decision, "Cadastre 2014 - A Vision for A Cadastral System in the Future" was published in 1998. This vision addresses about the future development of cadastre and consists of views for ensuring the cadastre to be globally integrative and shaping the future of surveying occupation. This paper discusses on the vision of Cadastre 2014, its implementation status in Nepal to evaluate Nepal's "Cadastre 2014" performance.